Relationship between plasma lactate parameters and muscle characteristics in female cyclists - Bishop, D.; Jenkins, D. G.; McEniery, M.; Carey, M. F. (Medicine & Science in Sports & Exercise, 2000)
Purpose: In a previous study, we showed that when six different plasma lactate parameters (LPs) were compared, the LP determined by the Dmax method was the best predictor of 1-h cycling performance in women. The present study extended these findings to determine whether or not the relationship between the following six LPs and endurance performance could be explained by their relationship with muscle fiber characteristics: 1) lactate threshold (LT; the power output at which plasma lactate concentration begins to increase above the resting level during an incremental exercise test), 2) LT1 (the power output at which plasma lactate increases by 1 mmol·L-1 or more), 3) LTD (the lactate threshold calculated by the Dmax method), 4) LTMOD (the lactate threshold calculated by a modified Dmax method), 5) L4 (the power output at which plasma lactate reaches a concentration of 4 mmol·L-1), and 6) LTLOG (the power output at which plasma lactate concentration begins to increase when the log([La-]) is plotted against the log(power output)). Methods: Twelve trained female cyclists (27.3 ± 5.4 yr) first completed an incremental cycle test to determine both their LPs and peak V(dot)O2. One week later, endurance performance was assessed as the average absolute power output maintained during a 1-h endurance test (OHT). Resting muscle was sampled by needle biopsy from m. vastus lateralis and analyzed for fiber type diameter, fiber type percentage, 2-oxoglutarate dehydrogenase (OGDH) activity, and phosphofructokinase (PFK) activity. Results: OHT performance was more strongly correlated with all LPs (r = 0.71-0.89, P < 0.05) than with peak V(dot)O2 (L·min-1, r = 0.65, P < 0.05). OGDH activity, PFK activity, and the percentage of Type I fibers were not related to peak V(dot)O2, any of the LPs, or OHT performance. The diameter of the Type II fibers, however, was negatively related to OHT performance (r = -0.77, P < 0.01) and to four of the LPs (r = -59 to -0.86, P < 0.001). Conclusions: These correlations, which indicate that large Type II fibers may impair endurance performance, may be the result of greater production and/or reduced removal of lactate from the larger, glycolytic Type II fibers. LPs most strongly correlated with Type II fiber diameter were also most strongly correlated with OHT performance.